Efficiency of PUFAs Incorporation from Marine Sources in Yolk Egg`s Laying Hens - de Carvalho, Paulo Reis; Pita, Maria Carolina Goncalves; Neto, Eduardo Piber; Mendonca Jr., Cassio Xavier de (International Journal of Poultry Science, 2009)
Two hundred eighty-eight 32-wk-old Hisex White laying hens were used in this research during a 10 week period, arranged in a 2 x 5 completely randomized factorial design, with three replicates of eight birds per treatment. Two groups: fish oil (OP) and Marine Algae (AM) with five DHA levels (120, 180, 240, 300 and 360 mg/100 g diet) were assigned including two control groups, birds fed corn and soybean basal diet (CON) and a diet supplemented with AM (AM420) to study the efficiency of egg yolk fatty acid enrichment. The Arachidonic Acid (AA), Linoleic (LA) and PUFAs n-6 mean values ranged, respectively, 98.71 mg, 987.70 mg and 1108.92 mg/yolk for the hens fed the CON diet and 38.87 mg, 734.22 mg and 802.79 mg/yolk for the OP360 group. The percentage of AA incorporation (% INC) in egg yolk decreased linearly with the increase of DHA levels in the diets supplemented with OP and AM, from 4.81% (CON) to 2.57% (OP360) and 3.51% (AM420). The efficiency (%) of DHA incorporation into the yolk decreased linearly with increasing of DHA levels in the diet supplemented with OP and AM, from 85.11% (OP120) and 65.28% (AM120) to 49.45% (OP360) and 34.06% (AM420). The levels of DHA in the egg yolk of birds supplemented with OP had significant increase from 22.64 mg/yolk (CON) to 187.91 mg/yolk in OP360 group. PUFAs n-3 means into the eggs were significantly (p<0.05) increased when the groups CON (62.16 mg/yolk) and OP360 (218.62 mg/yolk) were compared.